Case Report: Meningoencephalitis With Thrombotic Occlusive Vasculopathy in a Young EBV-Naïve Boy Is Associated With a Novel SH2D1A Mutation - Steininger, Jolanda; Rossmanith, Raphael; Geier, Christoph B.; Leiss-Piller, Alexander; Thonhauser, Lukas; Weiss, Simone; Hainfellner, Johannes A.; Freilinger, Michael; Schmidt, Wolfgang M.; Eibl, Martha M.; Wolf, Hermann M. (Frontiers in Immunology, 2021)
XLP1 is characterized by the inability in clearing EBV infections and immune dysregulation including vasculitis. We describe a boy with XLP1 presenting with non-EBV meningoencephalitis and cerebral vasculopathy, leading to multiple cerebral aneurysms and severe cerebral damage. We could demonstrate a novel SH2D1A mutation is associated with this rare clinical phenotype.